2013
DOI: 10.1113/jphysiol.2012.249235
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated glial cell line‐derived neurotrophic factor through cyclooxygenase‐2 activation in the muscle is required for mechanical hyperalgesia after exercise in rats

Abstract: Key points• Unaccustomed strenuous exercise that includes lengthening contraction often causes delayed onset muscle soreness (DOMS), characterised as muscular mechanical hyperalgesia.• It has been reported that bradykinin triggers upregulation of nerve growth factor in exercised muscle, sensitizing nociceptors and resulting in DOMS, but additional mechanism(s) may be involved.• We showed that pretreatment with cyclooxygenase (COX)-2 inhibitors completely suppressed the development of DOMS, but treatment 2 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
90
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 39 publications
5
90
1
Order By: Relevance
“…Nonetheless, as described before, a possibility is that BTJ might suppress the release of stimuli thought to sensitize nociceptive neurons in the muscle and ECM (Murase et al 2013), the latter of which, to the best of the current knowledge, is proposed as the main site where muscle pain originates (Crameri et al 2007). However, because muscle tissue samples could not be obtained in this study, this posit is somewhat speculative until confirmed by future studies; we acknowledge that our inability to collect muscle tissue and investigate these mechanisms is a limitation of this study.…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, as described before, a possibility is that BTJ might suppress the release of stimuli thought to sensitize nociceptive neurons in the muscle and ECM (Murase et al 2013), the latter of which, to the best of the current knowledge, is proposed as the main site where muscle pain originates (Crameri et al 2007). However, because muscle tissue samples could not be obtained in this study, this posit is somewhat speculative until confirmed by future studies; we acknowledge that our inability to collect muscle tissue and investigate these mechanisms is a limitation of this study.…”
Section: Discussionmentioning
confidence: 94%
“…A number of well-established proalgesic mediators are locally released in muscle after eccentric exercise and thus likely involved in DOMS, including pro-inflammatory cytokines [4], trophic factors [2,35,36] and prostanoids [12]. Importantly, after recovery from this hyperalgesia, rats exhibited attenuated muscle pain upon exposure to a second bout of eccentric exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, AOX effects might not be the main mechanism by which BTJ could benefit recovery; instead this could primarily be through anti-inflammatory effects or reduced proteolysis. In support of an anti-inflammatory mechanism, the betalains in beetroot have been shown to inhibit cyclooxygenase-2 (COX-2) activity, which, via synthesis of prostanoids, play a key role in the development of the acute inflammatory response (Vidal et al 2014), and have been linked to the development of muscle soreness (Murase et al 2013). …”
Section: Introductionmentioning
confidence: 99%